Greco-Roman Wrestling Techniques, Classification, Systematics and Their Terminology General Rules - Mehmonov Ravshan Nabiyevich; Oʻrmonova Izzatxon Mamatusuf qizi (Zien Journals, 2022)
The following points provide information and suggestions on Greco-Roman wrestling techniques, classification, systematics and terminology, and general rules
Keywords: Sports; health; wrestling; types of struggle